Trends of maternal mortality in a tertiary care hospital: a five year retrospective study - Singh, Leimapokpam Roshan; Devi, Khumanthem Pratima; Priyadarshinee, Lipsa; Singh, M. Rameswar; Devi, Yengkhom Mandakini; Krupa, Bandi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Maternal mortality is a measure of quality of health care in community. Maternal mortality ratio is a very sensitive index that reflect the quality of reproductive care provided to the pregnant women. The aims and objectives were to study the institutional maternal mortality, the causes of maternal death and the impact of COVID-19 on MMR. Methods: A retrospective hospital-based study of 38 maternal death was done over a period of 5 years from June 2016 to May 2021 in obstetrics and gynaecology department, RIMS Imphal. Details of all the mortalities were collected from individual case sheets, facility based maternal death review forms and MDR case summary. Results: A total of 38 deaths were analysed. MMR in the study period was 86 per 1 lakh live births. Maximum maternal deaths were reported in the age group of 30-34 years. Majority of maternal death were reported in multipara (57.9%) as compared to primipara (34.2%). Most of them were un-booked (63.2%) and belonged to rural areas (60.5%). The commonest cause was obstetrics haemorrhage (42.1%) followed by hypertensive disorders (23.6%). Acute respiratory distress syndrome associated with SARS-CoV-2 is one of the most important causes of increasing mortality rate (10.5%). Conclusions: Early identification of high-risk pregnancy, regular antenatal check-up and proper training of health personnel along with timely referral to tertiary care centre can help to reduce the mortality. There is an increase in MMR during the current pandemic 2020-2021.